From Interfacial Water to Macroscopic Observables: A Review - Alberto Striolo (Adsorption Science & Technology)
The scientific community has always been fascinated by the properties of water and, consequently, a number of investigations continue to address this ubiquitous fluid responsible for life on this planet. Interfacial water plays an important role in a number of physical phenomena that include protein-folding, structure/function relationships in enzymes, the design of nano-fluidic devices, and even macroscopic effects including drag reduction. Interfacial water is attracting renewed interest because of applications such as electrical double layer capacitors, and also for the microbial conversion of cellulose to biofuels. Current scientific explorations regarding interfacial water take advantage of innovations in experimental capabilities, theoretical models and computational tools. Particular attention has been devoted recently to uncovering the relationships between macroscopic properties, often summarized under the hydrophobic/hydrophilic characterization of solid surfaces, to the atomic-level behaviour of water near interfaces. The goal of the present review is to compile recent results obtained along these research objectives, for the most part obtained by simulation studies, to discuss some experimental techniques that appear most adequate to validate the simulation results (specular X-ray reflectivity, ultrafast IR spectroscopy, atomic force microscopy, and others), and to propose possible research topics to further develop this field. Because of our recent interests, the surfaces considered herein are mainly oxides.